Measurements of B(B̄0→Λc+p̄) and B(B- →Λc+p̄π-) and studies of Λc+π- resonances - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We present an investigation of the decays B̄0→Λc+p̄ and B-→Λc+p̄π- based on 383×106 Υ(4S) →BB̄ decays recorded with the BABAR detector. We measure the branching fractions of these decays; their ratio is B(B-→Λc+p̄π-)/ B(B̄0→Λc+p̄)=15.4±1.8±0.3. The B-→Λc+p̄π- process exhibits an enhancement at the Λc+p̄ threshold and is a laboratory for searches for excited charm baryon states. We observe the resonant decays B-→Σc(2455)0p̄ and B-→Σc(2800)0p̄ but see no evidence for B-→Σc(2520) 0p̄. This is the first observation of the decay B-→Σc(2800) 0p̄; however, the mass of the observed excited Σc0 state is (2846±8±10)MeV/c2, which is somewhat inconsistent with previous measurements. Finally, we examine the angular distribution of the B-→Σc(2455)0p̄ decays and measure the spin of the Σc(2455)0 baryon to be 1/2, as predicted by the quark model. © 2008 The American Physical Society.